Switching up sides: Using choice architecture to alter children's menus in restaurants. (1st January 2022) - Ferrante, Mackenzie J.; Johnson, Susan L.; Miller, Jeffrey; Bellows, Laura L.
Abstract: U.S. children's frequent consumption of restaurant foods has been associated with low vegetable consumption. Use of choice architecture in restaurants has been shown to increase children's orders of healthy sides, but what children consume when healthy sides are included is unknown. The purpose of the present study was to investigate whether altering the choice architecture of children's meals by restructuring the menu, using optimal defaults and vice-virtue bundles, would impact ordering of side dishes and consumption of a vegetable side dish during a restaurant meal. Families with a child between 4-8y attended three dinners at a university-based restaurant. Children's meals included choice of entree (macaroni-and-cheese or chicken tenders) and default side: all carrots (150 g; Menu-1), small fries (50 g)/large carrots (100 g; Menu-2), and small carrots (50 g)/large fries (100 g; Menu-3). Participants could opt-out of the default side for: only fries (Menu-1) or only fries or carrots (Menus-2/3). All foods were pre- and post-weighed to determine consumption. Descriptive statistics examined children's ordering behavior. Repeated measures ANOVA examined differences in consumption of study foods. A paired samples t -test examined differences in french fry consumption (Menus-2/3). Forty-eight children (6.2 ± 1.3 years; 25 male) participated. Most children remained with the default side (Meal-1: 90%; Meal-2: 88%; Meal-3: 85%). Significant differences were seen in children's consumption of french fries (t = −2.57, p  = .014) where children ate more during meal 3 compared to meal 2. There were no significant differences in carrot consumption. Use of optimal defaults led to increased orders of healthy sides and steady consumption across the meal conditions. However, use of an optimal, vice-virtue bundle led to a decrease in consumption of french fries. Further investigation of optimal default use on children's menus is warranted.